Pengaruh Gaya Kepemimpinan dan Kompensasi terhadap Kinerja melalui Motivasi Aparatur Sipil Negara pada Biro Organisasi Sekretariat Daerah Provinsi Jambi - Abdillah Abdillah; Saiyid Syeikh; Fakhrul Rozi Yamali (Universitas Batanghari Jambi, 2024)
This research aims to further examine the influence of leadership style and compensation on performance through ASN motivation at the Jambi Province Regional Secretariat Organization Bureau. This research is descriptive research with a survey method. The sample used was 62 respondents consisting of all ASN at the Jambi Province Regional Secretariat Organization Bureau. Furthermore, the data collected through distributing questionnaires was analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS-SEM). The results of the research show that the description of leadership style variables and compensation variables is in the quite good category, motivation variables and performance variables are in the quite high category. The results of data processing showed that the compensation variable had a positive and insignificant effect on performance, but compensation had a positive and significant effect on the motivation variable. The motivation variable has a positive and significant effect on performance, the leadership style variable has a positive and significant effect on employee performance through motivation and compensation has a positive and significant effect on performance through motivation at the Jambi Province Regional Secretariat Organization Bureau